Myoglobin-loaded gadolinium nanotexaphyrins for oxygen synergy and imaging-guided radiosensitization therapy - Ma, Xiaotu; Liang, Xiaolong; Yao, Meinan; Gao, Yu; Luo, Qi; Li, Xiaoda; Yu, Yue; Sun, Yining; Cheng, Miffy H. Y.; Chen, Juan; Zheng, Gang; Shi, Jiyun; et al. (Nature communications, 2023)
Gadolinium (Gd 3+ )-coordinated texaphyrin (Gd-Tex) is a promising radiosensitizer that entered clinical trials, but temporarily fails largely due to insufficient radiosensitization efficacy. Little attention has been given to using nanovesicles to improve its efficacy. Herein, Gd-Tex is transformed into building blocks “Gd-Tex-lipids” to self-assemble nanovesicles called Gd-nanotexaphyrins (Gd-NTs), realizing high density packing of Gd-Tex in a single nanovesicle and achieving high Gd-Tex accumulation in tumors. To elucidate the impact of O 2 concentration on Gd-Tex radiosensitization, myoglobin (Mb) is loaded into Gd-NTs (Mb@Gd-NTs), resulting in efficient relief of tumor hypoxia and significant enhancement of Gd-Tex radiosensitization, eventually inducing the obvious long-term antitumor immune memory to inhibit tumor recurrence. In addition to Gd 3+ , the versatile Mb@Gd-NTs can also chelate 177 Lu 3+ (Mb@ 177 Lu/Gd-NTs), enabling SPECT/MRI dual-modality imaging for accurately monitoring drug delivery in real-time. This “one-for-all” nanoplatform with the capability of chelating various trivalent metal ions exhibits broad clinical application prospects in imaging-guided radiosensitization therapy. Researchers have been working on radiosensitizers to improve radiotherapy efficacy. Here the authors generate gadolinium nanotexaphyrins (Gd-NTs) that self-assemble and further load it with myoglobulin to relieve hypoxia, improve radiosensitization effects of Gd-coordinated Texaphyrin, and suppress tumor recurrence.